3 or 4 things I know about the audiovisual essay, or the pedagogical perils of constructive alignment. Issue 1 (2nd January 2021) - D'Cruz, Glenn
ABSTRACT: In general terms, this paper situates the audiovisual-essay within current debates about the institutional viability of practice based research and argues that the video-essay as a form can unsettle verities about the relationship between creative play and scholarly knowledge within the university. It also makes a case for adopting an expanded conception of writing informed by Jacques Derrida's account of grammatology as an integral strategy for legitimating the audiovisual essay as an assessment tool. The paper also contests assumptions about what constitutes effective pedagogy in constructive alignment, a theory of educational measurement currently in-vogue in academic institutions.